Workspace Analysis of Hydraulic Follow-up Arm based on Monte Carlo Method - Pengyun Feng; Liangbin Zhan; Yanping Xiao; Tiancheng Huang (Jixie chuandong)
Taking the hydraulic follow-up arm of a company as the research object， an improved D-H coordinate system is established， and a 3D workspace of the end-effector of the hydraulic follow-up arm is solved by the forward kinematics equation. Based on Monte Carlo method and extreme value theory， the working face at the height of fracturing wellhead is solved， and the influence of the arm length of hydraulic servo arm on the stopping distance and working width is studied under the condition of fixed stopping error. The results show that， under the fixed stopping error， when the current arm length is greater than or equal to the rear arm length， with the extension of the front arm of the hydraulic follow-up arm， the equal slope of the stopping distance increases， and the working width is basically stays unchanged. With the extension of the large arm after the hydraulic follow-up arm， the parking distance is basically stays unchanged， but the slope such as the working width becomes wider. On this basis， a reasonable interface height is proposed to alleviate the large difference between the two arms. The research results can provide theoretical reference for the optimization design of the hydraulic follow-up arm.